Percepção de alunos de ensino fundamental sobre o parque estadual Delta do Jacuí e seu entorno - Dal Bosco, Caroline Araújo (2011)
Considering the importance of developing environmental projects and educational initiatives at the local level, this study sought to identify and analyze previous knowledge of students about the Delta Jacuí State Park and its surroundings. To this end, we used a predominantly qualitative research, having as subject students in a class of 5th grade, 6th grade, in a State Primary School in the municipality of Eldorado do Sul, which is situated within the boundary of Protected Area Delta State Environmental Jacuí (APAEDJ) and the nearby State Delta Park Jacuí (PEDJ). In this context, there was development and monitoring of activities, systematic records to identify the environmental perception of the participants expressed during the activities, both individually and in group. Data were collected through three surveys on students' prior knowledge: (1) what they knew about the Delta Jacui State Park and its surroundings, from a semi-structured questionnaire; (2) what they knew about the environment, by means of written description, drawing and oral presentation environment design; and (3) what they thought about local environmental issues and their possible solutions through discussions in small groups and implementation of practical activity "Web of Environmental Problems", and the responses were plotted and interpreted. As analysis methodology was used Textual Discourse Analysis. Among other results, it was revealed that these students were not familiar with terminology such as "conservation area", "State Park" and "Environmental Protection Area", but understood that they referred to places geared to care for and / or preserve the environment, nature, plants and animals. They highlighted the environmental problem of waste present both local (APAEDJ) and in the Park (PEDJ). Possible solutions proposed to this problem involves not only preventive measures and ways to mitigate the damaged one, which is in the representation of the environment prevailing in the study subjects. This representation is globalizing, which shows the relationship of reciprocity between nature and society. The environment is not only seen as a resource, but as something to be conserved and preserved for present and future generations, humans being perceived not as mere observers, but as an integral part of that reality and modifier.